Sosialisasi Pemberdayaan Situs Geologi untuk Pengembangan Wisata Desa Purwodadi, Malang - Susilo, Adi; Pamungkas, Mauludi Ariesto; Juwono, Alamsyah M.; Naba, Agus; Yudianto, Didik; Hasan, Muhammad Fathur Rouf (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Jakarta, 2024)
Purwodadi Village is located in the southern part of Malang Regency with a karst area which presents a beautiful panorama of rock outcrops and forms a collection of geological sites, so this area has the potential to be developed as a geotourism. Optimizing the use of geological sites and digital technology in the tourism sector will bring extraordinary benefits. This service activity aims to socialize the empowerment of geological sites to support Purwodadi Tourism Village as a geotourism centre. This activity is in collaboration with the Purwodadi Village-Owned Enterprise